Specific surface area and electron donating capacity determine biochar's role in methane production during anaerobic digestion. (May 2020) - Qin, Yong; Yin, Xiaosi; Xu, Xingkun; Yan, Xiangrui; Bi, Feng; Wu, Weixiang
Graphical abstract: Highlights: Woody biochars performed much better than herbal ones in biomethanization. The SSA and EDC were the key properties of biochar for AD stimulation. Glucose decomposting bacteria increased with the increasement of SSA and EDC. Abstract: The addition of biochar derived from different materials can have varying effects on anaerobic digestion (AD), depending on its physicochemical properties. Physicochemical properties of biochars, biomethanization performance and microbial communities were examined to evaluate the effectiveness of biochars made from different plant wastes on AD in this study. Results showed that all biochars significantly reduce the lag phases during AD, compared with a control treatment (CK). Woody biochars particularly performed much better than herbal ones. Correlation analysis revealed that specific surface area (SSA) and electron donating capacity (EDC) were the key properties of the plant-feedstock-derived biochar in AD enhancement. Microbial community structure analysis showed that higher SSA and EDC are conducive for the growth of bacteria decomposing glucose, further promoting daily methane production in the early AD stage. The results indicate that it is important to select biochar with higher SSA and EDC to enhance biomethanization in AD systems.